C-13-urea breath test with infrared spectroscopy for diagnosing Helicobacter pylori infection in children and adolescents - Kawakami, Elisabetye [UNIFESP] (2002)
Background and Objective: Studies support the accuracy of C-13-urea breath test for diagnosing and confirming cure of Helicobacter pylori infection in children. Three methods are used to assess (CO2)-C-13 increment in expired air: mass spectrometry, infrared spectroscopy, and laser-assisted ratio analysis, in this study, the C-13-urea breath test performed with infrared spectroscopy in children and adolescents was evaluated.Methods: Seventy-five patients (6 months to 18 years old) were included. the gold standard for diagnosis was a positive culture or positive histology and a positive rapid urease test. Tests were performed with 50 mg of C-13-urea diluted in 100 mL orange juice in subjects weighing up to 30 kg, or with 75 mg of C-13-urea diluted in 200 mL commercial orange juice for subjects weighing more than 30 kg. Breath samples were collected just before and at 30 minutes after tracer ingestion. the C-13-urea breath test was considered positive When delta over baseline (DOB) was greater than 4.0%.Results: Tests were positive for H. pylori in 31 of 75 patients. Sensitivity was 96.8%, specificity was 93.2%, positive predictive value was 90.9%, negative predictive value was 97.6%, and accuracy was 94.7%. Conclusions: C-13-urea breath test performed with infrared spectroscopy is a reliable, accurate, and noninvasive diagnostic tool for detecting H. pylori infection. (C) 2002 Lippincott Williams Wilkins, Inc.